2023
DOI: 10.24875/gmm.m20000438
|View full text |Cite
|
Sign up to set email alerts
|

Uso de mioinositol más Bifidobacterium lactis y Lactobacillus rhamnosus para la prevención de diabetes mellitus gestacional en mujeres mexicanas

Abstract: Objetivo: Comparar la incidencia de diabetes mellitus gestacional (DMG) en mujeres con tres o más factores de riesgo para desarrollar DMG suplementadas con mioinositol más probióticos versus mujeres sin suplementación. Material y métodos: Estudio de cohorte retrospectivo, grupo 1, mujeres con suplementación (mioinositol 2 g más Bifidobacterium lactis y Lactobacillus rhamnosus 5x10 8 unidades formadoras de colonias, dos veces al día, de las 12-14 hasta las 28 semanas de gestación); grupo 2, mujeres con control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
6
1
1
Order By: Relevance
“…We did not have a control group without intensive MNT intervention to evaluate the benefit of intensive MNT alone. However, in a study that included participants in our institution with three or more risk factors for GDM without intensive MNT, the incidence of GDM using the IADPSG diagnostic criteria was 46.9% [ 29 ], which was higher than the incidence of GDM in this study and could be attributable to the early intervention in the present study.…”
Section: Discussioncontrasting
confidence: 65%
“…We did not have a control group without intensive MNT intervention to evaluate the benefit of intensive MNT alone. However, in a study that included participants in our institution with three or more risk factors for GDM without intensive MNT, the incidence of GDM using the IADPSG diagnostic criteria was 46.9% [ 29 ], which was higher than the incidence of GDM in this study and could be attributable to the early intervention in the present study.…”
Section: Discussioncontrasting
confidence: 65%
“…Probiotics are live microorganisms that bring health benefits to the host when administered in appropriate amounts [ 36 ]. The role of probiotics in preventing carbohydrate disorders and GDM is not yet fully understood or proved; however, there are several studies that show promising results [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…After the intervention, the frequency of GDM in the supplemented group was 29.2% and, in the control group, it was 47.9% (RR: 0.61; p = 0.03). The study concluded that supplementation with myo-inositol and probiotics starting at 12–14 weeks of pregnancy reduced the incidence of GDM in Mexican women [ 39 ]. Although the combination of myo-inositol and probiotics has been shown to be beneficial in preventing GDM, no clear conclusions can be drawn as to whether myo-inositol influences these results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…También se obtienen metabolitos de las bacterias, especialmente los ácidos grasos de cadena corta los que pueden actuar directa o indirectamente en las células intestinales (mediante la modificación del pH), regulando varios procesos como la carcinogénesis colorrectal, la absorción de minerales, y la eliminación de otras sustancias dañina al organismo humano. (Reyes-Muñoz, Sosa, Flores-Robles, Arce-Sánchez, Martínez-Cruz, & Gutiérrez-Castrellón, 2020), (Reyes-Muñoz, Sosa, Flores-Robles, Arce-Sánchez, Martínez-Cruz,Garduño-García, et al, 2020)…”
unclassified